NON PHARMACOLOGICAL MANAGEMENT OF PERINEAL WOUNDS IN POST PARTUM : A REVIEW OF LITERATURE - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim; Yanti Hermayanti (Journal of Maternity Care and Reproductive Health, 2021)
Most of the women who gave birth spontaneously experienced tears in the perineum, if not treated properly, it can slow wound healing, increase the size and depth of the wound which can lead to post partum infection. One of the ways to accelerate the healing of perineal wounds is by non-pharmacological management. This literature review aims to analyze the non-pharmacological management of perineal wounds in postpartum mothers. The database used is Google scholar, PubMed, and Scientdirect with the keywords: post partum OR post partum AND non-pharmacological wound care OR nonpharmacological intervention OR treatment OR therapy AND perineal wound OR perineal wound healing. Inclusion criteria used: articles published in the last 5 years, RCT method or quasi experiment or experiment, primary research and full text available. The search results were obtained from Google scholar 18,513 articles, PubMed 6 articles and Scientdirect 150 articles. After screening based on inclusion criteria obtained from Google scholar 8 articles, PubMed 1 article and Scientdirect 2 articles, then a feasibility study was carried out using The Joana Briggs Institute (JBI) and obtained 6 articles that met the requirements for analysis. The results of the analysis showed that several non-pharmacological treatments were effective in healing perineal wounds including the use of red betel leaf decoction, Kegel exercises, consumption of tamarind and turmeric water, the use of Hyperricum Perforatum oil, the use of Achillea Millefolium and Hypericum Perforatum ointment, and cold compresses. It is hoped that non-pharmacological management of perineal wounds will be an alternative to accelerate wound healing and prevent infection.